Interaction of Organizational Innovation Management and Consumer Value Perception in the Aviation Sector - Karaman, Fatih; Narci, Muhammed Talha (International Review of Management and Marketing, 2026)
This study examines the impact of organizational innovation management on consumer value perception in the aviation sector by focusing on product, strategy, process, and market innovation dimensions. A quantitative research design was employed, and data were collected through a survey conducted with working-age individuals (18-65 years old) in Turkey during January and February 2025. A total of 492 valid responses were obtained. The questionnaire included demographic items, the organizational innovation scale, and the perceived value scale. The study received ethical approval from Istanbul Medipol University (Decision No. 186, 2025). Findings reveal that product innovation positively affects emotional, functional, and economic value perceptions, while strategic innovation significantly impacts all value dimensions. Market innovation strongly influences economic value, and process innovation contributes only to functional value. These results highlight that organizational innovation management in aviation significantly shapes consumer perceptions and suggest that innovation efforts should be more consumer-centered to enhance satisfaction and loyalty. The study contributes to understanding how different innovation types influence consumer behavior and offers insights for aviation businesses aiming to improve their innovation orientation in a competitive market.